Research Progress of Silicon-Based Heterojunction Mid-Wave Infrared Photodetectors - Zeng Yuling, Feng Song, Ma Baoke, He Xinyi, Wu Jianyang, Li Haojie (Hangkong bingqi, 2024)
Mid-wave infrared photodetector is an important photoelectric detection equipment, which uses the photoelectric effect to convert infrared radiation into electrical signals. It is widely used in guidance, unmanned aerial vehicles, fighter jets and other platforms, and plays an important role in target detection, tracking and identification. Silicon-based heterojunction mid-wave infrared photodetectors are based on silicon materials, combined with mature silicon device technology and infrared detection performance, and have the advantages of low cost, easy preparation and high integration, becoming an opportunity to break through the bottleneck of traditional silicon-based optoelectronic devices. With the continuous progress of research, silicon-based heterojunction mid-wave infrared photodetectors have made great progress in various aspects, bringing new opportunities and challenges to infrared photoelectric detection technology. In this paper, the research and development of new germanium/silicon, graphene/silicon and other silicon-based heterojunction mid-wave infrared photodetectors are discussed, and the advantages of detectors of different materials are analyzed and compared.